[P208] Geometric and dosimetric comparison of four intrafraction motion adaptation strategies for stereotactic liver radiotherapy. (August 2018) - Poulsen, Per; Nankali, Saber; Hansen, Rune; Weber, Britta; Høyer, Morten; Worm, Esben
Abstract : Purpose: The accuracy of stereotactic body radiotherapy (SBRT) is limited by tumor motion. Selection of the most suitable motion mitigation strategy requires good understanding of the geometric and dosimetric consequences. In this study, we compare the geometric and dosimetric accuracy of four motion adaptation strategies for liver SBRT. Methods: Fifteen liver SBRT patients received respiratory gated IMRT or conformal treatments in three fractions. The CTV-PTV margin was 5 mm axially and 7–10 mm cranio-caudally. The CTV and PTV were covered with 95% and 67% of the prescribed mean CTV dose, respectively. The gating was guided by implanted electromagnetic transponders (Calypso) with a 3–4 mm gating window near full exhale. The time-resolved target position error was calculated during each treatment fraction for (1) the actual gated treatments and simulated treatments with (2) MLC tracking, (3) adaptation to intrafraction baseline drift by inter-field couch corrections in case the mean error exceeded 2 mm, and (4) adaptation to interfraction motion only by pre-treatment CBCT image-guidance. The geometric errors were used to calculate motion margins and motion-induced reductions in CTV D 95 relative to the planned dose ( Δ D 95 ). Results: The mean (range) number of couch corrections to compensate for tumor drift was 2.8 (0–7) with gating, 1.4 (0–5) with baseline shift adaptation, and zero for the other strategies. The motion margins were 3.5 mm (left–right), 9.4 mm (cranio-caudal) and 3.9 mm (anterior–posterior) without intrafraction motion adaptation, approximately half of that with baseline shift adaptation, and 1–2 mm with MLC tracking and gating. With 7 mm CC PTV margins the mean (range) of Δ D 95 was 8.1 (0.6–29.4)%-points (no intrafraction motion adaptation), 4.0 (0.4–13.3)%-points (baseline shift adaptation), 1.0 (0.3–2.2)%-points (MLC tracking) and 0.8 (0.1–1.8)%-points (gating). With 10 mm CC margins Δ D 95 was instead 4.8 (0.3–14.8)%-points (no intrafraction motion adaptation) and 2.9 (0.2–9.8)%-points (baseline shift adaptation). Conclusions: Baseline shift adaptation can mitigate gross dose errors without the requirement of real-time motion monitoring. MLC tracking and gating are, however, much more effective strategies ensuring high similarity between planned and delivered doses. Gating was slightly better than MLC tracking dosimetrically, but had lower duty cycle and required several couch corrections to maintain the tumor exhale position inside the gating window.